2019
DOI: 10.1037/rel0000155
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and ethnocultural empathy among Italian adolescents: The mediating role of religious identity formation processes.

Abstract: The current study examined the unique and combined roles of spirituality and religious identity formation processes on ethnocultural empathy among Italian youth. Spirituality was conceptualized as a desire for self-transcendence. Ethnocultural empathy entails concern for those of other cultural backgrounds. It was hypothesized that spirituality would predict ethnocultural empathy indirectly by way of religious identity commitment and in-depth exploration. Religious identity commitment is the extent to which pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 68 publications
(87 reference statements)
1
22
0
Order By: Relevance
“…Finally, the third process of the religious identity model (Crocetti et al, 2010; Iannello et al, 2019), reconsideration of commitment, referring to the efforts one makes to change no longer satisfactory present commitments, was not expected to have an impact on SWB (Karaś et al, 2015), and results confirmed our prediction.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Finally, the third process of the religious identity model (Crocetti et al, 2010; Iannello et al, 2019), reconsideration of commitment, referring to the efforts one makes to change no longer satisfactory present commitments, was not expected to have an impact on SWB (Karaś et al, 2015), and results confirmed our prediction.…”
Section: Discussionsupporting
confidence: 75%
“…Spirituality was assessed using the Italian version (Iannello et al, 2019) of the 28-item Spirituality Assessment Scale (Howden, 1992). Items were rated on a 6-point scale from 1 (strongly disagree) to 6 (strongly agree) and belonged to four different subscales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into consideration and measuring other aspects of self-concept, such as identities relating to culture, ethnicity, race, gender, or religion, could have provided us with a wider understanding of this issue. To explore these aspects of the self, it would have been necessary to adopt other existing scales validated for an Italian speaking population, but there appears to be a lack of these measures with a sole religious identity measure [ 35 ] recently validated. On the other hand, it would have been possible to validate more general measures of self-concept for the Italian context, such as the Tennessee Self-concept scale (TSCS-2 [ 36 ]), but we considered a priority for the Italian sporting context the translation of the AIMS, which is a scale specific for the sport domain and has received widespread use across several countries [ 10 13 ].…”
Section: Discussionmentioning
confidence: 99%